Role of dynamic hip screw with locking side plate in intertrochanteric fractures in elderly patients - Gurudatta, Harjot Singh; Arora, R. K.; Khanna, Gagan; Johal, Karandeep Singh; Singh, Deepinder; Bhardwaj, Aditya (International Journal of Research in Orthopaedics, 2020)
Background: Dynamic hip screw (DHS) is a vital mainstay implant in managing intertrochanteric fractures. While most of the modifications of implant have been done in screw design, this study evaluates the role of employing locking side plate with DHS to increase the screw hold and avoid plate pull out in trochanteric fractures of elderly patients. Methods: A prospective study was conducted from August 2012 to August 2014 on 30 patients having trochanteric fractures. The fixation, fracture consequences, functional outcome and complications were assessed clinically and radiologically in immediate post-operative period and on follow-ups at six weeks, three months, six months and one year. Young patients (<55 years), fractures with subtrochanteric extension and pathological fractures were excluded from study. Fractures in elderly patients from AO 31A1.1 to AO 31A3.1 were included in study. Evaluation of the clinical outcome was done by modified Harris hip score at the last follow-up. Results: Average age of the patients in study was 64 years; males had better outcome scores, which was statistically significant. The mean trauma-surgery interval was four days. Trauma surgery interval and functional outcome by Harris hip score was statistically significant and was inversely proportional. Union was achieved in all patients with delayed union noted in four cases; the average time to union was 12.2 weeks with no major complications and good functional outcome by Harris hip score. Conclusions: This study suggests that locking side plate with DHS would make a stronger bone implant construct and a valuable modification to prevent sliding, screw cut-out and side plate pull-out with low infection rates.